Biznes v Rossii . Biznes v Rossii . Business in Russia . Бизнес в России - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. The development of the tourism industry in Russia; segment on the success of Mikhail Zvezdinskii, a singer in the style of "Russian chanson"; privatization auctions. Featured in the program: Zvezdinskii, Mikhail (Singer) Contributors: Kotsiuba, Vera (Anchor) Развитие туристической отрасли в России; бизнес исполнителя русского шансона Михаила Звездинского; приватизационные аукционы. В программе участвуют: Звездинский, Михаил (Певец) Создатели: Коцюба, Вера (Ведущий/Ведущая)